2017
DOI: 10.1016/j.ymeth.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Imaging flow cytometry analysis of intracellular pathogens

Abstract: Imaging flow cytometry has been applied to address questions in infection biology, in particular, infections induced by intracellular pathogens. This methodology, which utilizes specialized analytic software makes it possible to analyze hundreds of quantified features for hundreds of thousands of individual cellular or subcellular events in a single experiment. Imaging flow cytometry analysis of host cell-pathogen interaction can thus quantitatively addresses a variety of biological questions related to intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 127 publications
1
48
0
Order By: Relevance
“…It has been previously reported that Acanthamoebae are able to reactivate VBNC Legionella pneumophila into an active pathogenic state . As shown in Figure A, VBNC cells cocultured within trophozoites appeared to revert to a culturable state, and that coculture with amoebae led to a 3‐log increase ( P < 0.0001) of culturable P. aeruginosa after 2 h. With slower kinetics, similar results were also obtained without amoeba due to the temperature upshift .…”
Section: Resultssupporting
confidence: 82%
“…It has been previously reported that Acanthamoebae are able to reactivate VBNC Legionella pneumophila into an active pathogenic state . As shown in Figure A, VBNC cells cocultured within trophozoites appeared to revert to a culturable state, and that coculture with amoebae led to a 3‐log increase ( P < 0.0001) of culturable P. aeruginosa after 2 h. With slower kinetics, similar results were also obtained without amoeba due to the temperature upshift .…”
Section: Resultssupporting
confidence: 82%
“…1d). The Bright Detail Similarity (BDS) score of colocalization between the uorescent signals of the SDCs and SARS-CoV-2 also showed a high degree of colocalization (generally, a BDS score of 2 or greater represents a high degree of overlap 68 ), especially in SDC3 and 4 transfectants ( Fig. 1d).…”
Section: ]) Colocalization Studies Revealed a Signi Cant Degree Of Cmentioning
confidence: 91%
“…Values of p<0.05 were accepted as signi cant 45,46 . During imaging ow cytometry, the IDEAS™ feature Bright Detail Similarity (BDS) was used to measure colocalization between two signals 68 The difference of SARS-CoV-2 internalization in A549 and K562 cells. WT A549 and K562 cells were incubated with heat-inactivated SARS-CoV-2 (at 1 MOI) for 18h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Since last 10 years, this approach has been increasingly used to study aspects of red cell morphology (Samsel et al, ) and has been used in many hematological studies such as erythroid cell biology (Samsel & McCoy, ), in the megakaryocyte cell biology and pathology (Niswander, McGrath, Kennedy, & Palis, ), also in the assessment of projected surface area, volume and morphological changes in the stored red blood cells in the blood bank (Roussel et al, ). This method is also used in the study of the intracellular pathogen (Haridas, Ranjbar, Vorobjev, Goldfeld, & Barteneva, ). Mantel and colleagues used IFC to study erythrocyte‐derived microvesicles in human malaria infections (Mantel et al, ).…”
Section: Introductionmentioning
confidence: 99%